E-SERVICE QUALITY AND E-RECOVERY SERVICE: EFFECTS ON PERCEIVED VALUE AND LOYALTY INTENTION OF DANA APPLICATION USERS - Gaffar, Mohammad Rizal; Fajar, Kurnia; Suryana, Marceilla; Febrianty, Ilma Amilia; Susanto, Eko (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
DANA is one of the electronic-based financial applications that supports non-cash transactions. It has the second-largest total users in Indonesia. However, users have complained about this application's quality of service and recovery. This research aims to determine the mediating effect of perceived value on e-service quality and e-recovery service towards loyalty intention. This research uses a quantitative method with a purposive sampling technique. The sample in this research is 164 respondents. PLS-SEM is used to analyze the model. The results of this research indicate that e-service quality has a direct and significant effect on perceived value. E-recovery service does not have a direct positive and significant effect on perceived value. Furthermore, there is no mediating effect of perceived value on e-service quality and e-recovery service towards loyalty intention.Â Keywords: e-service quality; e-recovery service; loyalty intention; perceived value